2007
DOI: 10.1017/s0014479706004601
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF EXPERIMENTAL VARIETIES FROM RECURRENT SELECTION FOR STRIGA RESISTANCE IN TWO EXTRA-EARLY MAIZE POPULATIONS IN THE SAVANNAS OF WEST AND CENTRAL AFRICA

Abstract: A breeding programme for resistance to Striga hermonthica in maize (Zea mays) was initiated in Côte d'Ivoire in 1994. Two extra-early populations, white (TZEE-W Pop STR) and yellow (TZEE-Y Pop STR), were formed from diallel crosses of the best adapted extra-early maturing maize germplasm in the West and Central African subregion. In an effort to improve the populations for Striga resistance, TZEE-W Pop was crossed to inbred 1368 STR (Tzi 3 STR), and TZEE-Y Pop to 9450 STR (Tzi 25 STR). The resulting F 1 popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 8 publications
8
42
2
Order By: Relevance
“…This result is consistent with those reported for selected IITA lowland early maturing varieties and inbred lines under Striga-infested and Striga-free conditions in WCA (Badu-Apraku et al, 2007). Due to the minor importance of GCA and the overdominating SCA, no inbreds with signifi cantly higher GCA than others could be identifi ed and there were no inbreds that could be considered as ideal testers in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with those reported for selected IITA lowland early maturing varieties and inbred lines under Striga-infested and Striga-free conditions in WCA (Badu-Apraku et al, 2007). Due to the minor importance of GCA and the overdominating SCA, no inbreds with signifi cantly higher GCA than others could be identifi ed and there were no inbreds that could be considered as ideal testers in this study.…”
Section: Discussionsupporting
confidence: 91%
“…For example, four out of the nine inbred lines used in this study were derived from TZE Comp5 C6S6 and are known to possess high levels of Striga resistance and therefore there could have been lack of independent distribution of the Striga resistance genes in these parental lines. It is also worth noting that the tester groups identifi ed in this study using GGE biplot were not close to the heterotic groups established on the basis of multivariate analysis by Badu-Apraku et al (2007). Yan and Hunt (2002) reported that a potential constraint of the biplot method is that it may not explain all of the variation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The breeding methodology employed for the development of Striga-resistant and drought-tolerant populations and cultivars (second generation of early cultivars) in the program during the West and Central Africa Collaborative Maize Research Network (WECAMAN) era has been described in detail by Badu-Apraku et al (2007, 2009. Briefly, two Strigaresistant and/or drought-tolerant early-maturing (90-95 d to maturity) populations, one white (TZE-W Pop DT STR) and the other yellow (TZE-Y Pop DT STR), were the main sources of drought-tolerant and/or Striga-resistant cultivars developed for the drought-prone and Striga-endemic environments in WCA.…”
Section: Development Of Drought-tolerant and Strigaresistant Populatimentioning
confidence: 99%
“…Results of a similar study by Menkir et al (2012b) involving the assessment of the reaction patterns of eight open-pollinated intermediate maturing cultivars in Abuja and Mokwa, Nigeria, under artificial Striga infestation showed consistency in the reactions of the cultivars across environments. Despite the efforts to reduce GEI and hence improve the stability of performance of the products from our breeding program, recent studies by Badu-Apraku et al (2006, 2008 and Badu-Apraku and Lum (2010) have revealed significant GEI for most traits under Striga infestation. This indicates that the cultivars responded differently to the environments and that the differential response among cultivars was due to varying climatic conditions, soil type, and crop management practices at diverse test locations, which might have significantly influenced infestation and subsequent growth and development of Striga.…”
mentioning
confidence: 99%